PENERAPAN ELEMEN-ELEMEN INTEGRATED REPORTING PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Kustiani, Nur Aisyah (JURNAL INFO ARTHA, 2016)
This study aims to determine whether the required elements in the integrated reporting (IR) initiatedby the IIRC has been fulfilled by companies listed on the Indonesia Stock Exchange (BEI). This study is aquantitative study using descriptive statistics of score value of IR elements identified from the reportsand information published through the company 's financial statements, annual reports, sustainabilityreports, and the information presented in the company's website.The results show that, in general, the companies listed on the BEI has met an average of 50 % of therequired elements. It indicates that the companies listed on the Stock Exchange have voluntarily reportednecessary information including financial information and some non-financial information aboutcorporate social and environmental liabilities. This finding also indicates if the capital market authority